Clarification of the Training Requirements for Working on Electric Vehicles - Fechtner, Heiko; Saes, Karl-Heinz; Fechtner, Erik; Braun, Tobias; Schmülling, Benedikt (International Journal of Advanced Corporate Learning (iJAC), 2016)
The dwindling energy resources and the compliance of international climate protection goals lead to a rethink in the automobile sector. One result of this rethink is the increasing distribution of electric vehicles in the last years. This development includes a new challenge for the training sector. For example, the implementation of a high-voltage system into automobiles involves a new hazard potential for people, who work on electric vehicles. Therefore, the employees in the areas of vehicle repair trade, rescue services, towing services, and other relevant sectors need a good qualification for working on electric vehicles. On the one hand, a lot of specialized training programs have already been developed in the area of academic education. On the other hand, there is a great need of training programs for professionals (e.g. motor mechanics, firefighters). Hence, this paper clarifies the current requirements in the education sector and the new hazard potential by working on electric vehicles. Moreover, an approach for the development of a specialized training program for working on electric vehicles is presented in this paper as well. The focus of this training program is on the improvement of the learning process by a blended learning concept with an adaptive modular design.